2019
DOI: 10.3390/molecules24081614
|View full text |Cite
|
Sign up to set email alerts
|

Carpesium divaricatum Sieb. & Zucc. Revisited: Newly Identified Constituents from Aerial Parts of the Plant and Their Possible Contribution to the Biological Activity of the Plant

Abstract: Carpesium divaricatum Sieb. & Zucc. has a long history of use as both a medicinal and a food plant. However, except for terpenoids, its chemical constituents have remained poorly investigated. The composition of hydroalcoholic extract from aerial parts of C. divaricatum was analyzed by HPLC-DAD-MSn, revealing the presence of numerous caffeic acid derivatives that were formerly unknown constituents of the plant. In all, 17 compounds, including commonly found chlorogenic acids and rarely occurring butyryl an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Compound 52 was identified as tricaffeoylhexaric acid, based on the molecular ion at m / z = 695 and characteristic product ions at m / z = 533, 371 and 209. The proposed identification is in accordance with the literature, as this rare derivatives have been reported before for Asteraceae [ 26 , 27 ]. Similarly, compound 22 , with a molecular ion at m / z = 533, was putatively identified as dicaffeoylhexaric acid.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Compound 52 was identified as tricaffeoylhexaric acid, based on the molecular ion at m / z = 695 and characteristic product ions at m / z = 533, 371 and 209. The proposed identification is in accordance with the literature, as this rare derivatives have been reported before for Asteraceae [ 26 , 27 ]. Similarly, compound 22 , with a molecular ion at m / z = 533, was putatively identified as dicaffeoylhexaric acid.…”
Section: Resultssupporting
confidence: 89%
“…The fragment at m / z = 585 was produced after a glucose/caffeoyl moiety loss (162 Da) but our attempt in its identification was just as unsuccessful. Namely, the only relevant report with that molecular ion was for isobutyryl diCQA, published by Kłeczek et al [ 27 ], which together with 162 Da, does produce the observed molecular ion. However, the molecular formula corresponding to either isobutyryl diCQA glycoside (C 29 H 30 O 13 ) or isobutyryl triCQA (C 34 H 30 O 15 ) does not match the observed most probable molecular formula, which was calculated as C 34 H 36 O 19 .…”
Section: Resultsmentioning
confidence: 99%
“…Peaks 4, 10, 13, 14 and 16, representing compounds which showed cleavage of two, three or four caffeoyl [M − H − (2–4 × 162)] − moieties resulting in m / z 209 fragments, were assigned to hexaric acid derivatives: di- O caffeoylhexaric acid (peak 4), tri- O -caffeoylhexaric acid (I) (peak 10), tri- O -caffeoylhexaric acid (II) (peak 13), tri- O -caffeoylhexaric acid (III) (peak 14) and tetra- O -caffeoylhexaric acid (peak 16). The compounds have been described earlier as constituents of other plants of the Asteraceae family, including systematically related species Inula helenium and Carpesium divaricatum [ 10 , 11 , 12 , 13 ]. The compound represented by peak 12 was an unknown derivative of dicaffeoylquinic acid judging from the presence of fragmentation ions at m / z 353, 335 and 179.…”
Section: Resultsmentioning
confidence: 99%
“…The compound represented by peak 18 ( m / z at 599 [M − H] − ), which demonstrated a similar fragmentation pattern to that of 17, except for the fact that the product ion at m / z 497 was generated by the cleavage of 2-methylbutyryl or 3-methylbutyryl (isovaleryl) instead of isobutyryl moiety [599 − C 4 H 9 COOH] − , could be envisioned as 2-methylbutyryl/isovaleryl-di-O-caffeoylquinic acid. The compound represented by the signal 19 was probably deoxy derivative of leontopodic acid, judging from the m / z value of its quasimolecular ion (765 [M − H] − ) and fragmentation ions at m / z 603 and 441 [ 13 , 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation